Kesihatan Mental dan Motivasi Pelajar UNISSA Terhadap Pembelajaran dalam Talian Semasa Pandemik Covid-19: Mental Health and UNISSA’s Students Motivation in Online Learning during Pandemic Covid-19 - Abdul Rahman, Ummi Fa’izah; Asmad, Arman (Journal of Al-Tamaddun, 2023)
This study aims to identify the level of mental health and the level of motivation among undergraduate students of UNISSA during online learning during the COVID-19 pandemic. This quantitative study uses a descriptive survey method through a questionnaire. A systematic random sampling method was used to obtain 584 undergraduate students from UNISSA students as a study sample. The General Health Questionnaire (GHQ-12) is used to measure students’ mental health levels while the Learning Motivation Strategies Questionnaire (MSLQ) is used to measure students’ motivation levels. The data obtained was analyzed using descriptive and inferential statistics. The findings of the study found that undergraduate students have a moderate level of mental health and a high level of motivation while following online learning during the COVID-19 pandemic. This study is expected to contribute to students, lecturers and Higher Education Institutions in understanding the importance of maintaining good mental health during the pandemic. The findings of this study also found that UNISSA’s role as an Islamic university in providing support to students was clearly proven, especially in difficult circumstances during COVID-19.